2006
DOI: 10.1111/j.1742-4658.2006.05529.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas6 and protein S

Abstract: Gas6 and protein S are two homologous secreted proteins that depend on vitamin K for their execution of a range of biological functions. A discrete subset of these functions is mediated through their binding to and activation of the receptor tyrosine kinases Axl, Sky and Mer. Furthermore, a hallmark of the Gas6–Axl system is the unique ability of Gas6 and protein S to tether their non receptor‐binding regions to the negatively charged membranes of apoptotic cells. Numerous studies have shown the Gas6–Axl syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
141
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(150 citation statements)
references
References 116 publications
3
141
0
Order By: Relevance
“…Both Gas6 and protein S are common ligands for the Tyro 3 RTK subfamily (Hafizi & Dahlback 2006a). It has been reported that phagocytic clearance of apoptotic cells by macrophages is mediated by Mer (Scott et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Gas6 and protein S are common ligands for the Tyro 3 RTK subfamily (Hafizi & Dahlback 2006a). It has been reported that phagocytic clearance of apoptotic cells by macrophages is mediated by Mer (Scott et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Each of the three members is composed of two N-terminal immunoglobulin-like domains and two fibronectin type III repeats in their extracellular regions. Two highly similar vitamin K-dependent proteins, Gas6 (product of growth arrestspecific gene 6) and protein S (a negative regulator of blood coagulation), are the biological ligands of the Tyro 3 RTK subfamily (Hafizi & Dahlback 2006a). These receptors and their ligands are widely expressed in cells of the immune, nervous, vascular, and reproductive systems.…”
Section: Introductionmentioning
confidence: 99%
“…Gas6, a paralog of protein S, promotes survival and proliferation of various types of cells by activating members of the Axl subfamily of receptor tyrosine kinases. These activities are abrogated when Gas6 is produced in the presence of warfarin, highlighting the indispensable nature of ␥-glutamyl carboxylation (19)(20)(21)(22). Additional evidence that Gla domains perform functions unrelated to hemostasis is provided by the recent identification of Gla domain proteins in ascidians, marine invertebrates that lack a blood coagulation cascade (23)(24)(25).…”
mentioning
confidence: 99%
“…The TAM RTK subfamily was identified most recently and contains three members -TYRO3, AXL, and MER (Hafizi & Dahlback 2006b). Two highly homologous vitamin K-dependent proteins, product of growth arrest-specific gene 6 (Gas6) and protein S (a negative regulator of blood coagulation) are the common ligands of TAM RTKs (Hafizi & Dahlback 2006a). Studies using gene knockout models have provided direct insights into the physiological functions of TAM RTKs (Lemke & Rothlin 2008).…”
Section: Introductionmentioning
confidence: 99%